INCREASING THE INCOME OF MSMES ACTORS THROUGH DIGITALIZATION: A STUDY CASE IN KOTA PARI VILLAGE - Lubis, Rizal P.; Fadlan, Ahmad; Sadewo, Aji (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
A significant trend in the business sector that arose in reaction to the advancement of information and communication technology (ICT) is the digitization of micro, little, and medium-sized enterprises (MSMEs). One important endeavor to help MSMEs' growth and competitiveness in the digital age is the digitalization of MSMEs through e-commerce. Here are some advantages and strategies for using e-commerce to digitalize MSMEs. MSMEs can take advantage of digital potential for long-term company growth with the correct tactics. There are numerous coastline tourism attractions in Kota Pari, including Mutiara 88 Beach, Woong Rame Beach, and Pondok Permai Beach. Because of this, Kota Pari is a popular tourist attraction. The marketing of MSME goods made in Kota Pari may benefit from this potential. Presenting the advantages and disadvantages of digitization for MSMEs is the aim of this study. The instance of Kota Pari village was also highlighted. Using library research and literature study techniques, this study took a qualitative descriptive approach. According to the study's findings, MSMEs players' income has been shown to rise when their products are promoted through digital marketing, technology-based initiatives like the Internet of Things, and operational and non-operational activities. The digital transformation process, however, may be complex and often challenging for MSMEs. Among the primary problems MSMEs face are limitations in their financial and human resources.